In the Archeology of Insult - عباس مطر . ناجي (Journal of College of Education, 2021)
Insult is a strategy of domination whose fundamental aim is to exhaust the symbolism upon which the resistance of the other is built. Jean-Jacques Rousseau believes that insult is a natural progression in human relations and the cultural understanding of the reality of life, as “people did not begin to appreciate each other in exchange, and the idea of ​​consideration barely formed in their souls, until each claimed The existence of a right to him in that, and it became impossible to deny that to anyone without punishment, and from here arose the first duty of etiquette even among the barbarians, and from here every mistake became an insult, because the humiliation he saw in the evil that results from insulting contempt for his person is more painful than evil Thus, as everyone was rewarded for the contempt directed at him by an estimated amount, the revenge became enormous, and the people became cruel and thugs, and thus it appears as a functional need that crystallizes as a result of the cultural clash between people..